The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Microalgal Biotechnology 2018
DOI: 10.5772/intechopen.74134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrodynamic Conditions of Photobioreactors on Lipids Productivity in Microalgae

Abstract: This research presents the effect of hydrodynamic conditions at different rates of aeration (1.4, 1.8, and 2.3 vvm) and the geometry of two photobioreactors with internal lighting on lipid productivity and other parameters of Chlorella vulgaris. A two-step nitrogenreduction cultivation mode was applied for promoting lipid accumulation. The inoculum was cultivated initially at 90 mg L −1 N-NH 4 + , and at the end of the exponential phase, it was fed to 11 L photobioreactor at 20 mg L −1 of N-NH 4 +. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The microalgae cultivation can be done in open systems such as open-ponds or closed systems named photobioreactor 8) . Both systems require the intensity of light as a critical factor affecting the growth 9) .…”
Section: Introductionmentioning
confidence: 99%
“…The microalgae cultivation can be done in open systems such as open-ponds or closed systems named photobioreactor 8) . Both systems require the intensity of light as a critical factor affecting the growth 9) .…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that aeration directly affects the hydrodynamic conditions in the culture medium while changing the concentrations of CO 2 . Some studies have shown that hydrodynamic conditions affect the growth, Responsible Editor: Ta Yeong Wu physiology, and lipid content of microalgae (Heredia et al 2018;Lee et al 2019). Hondzo and Wang (2002) found that Spirogyra had the largest biomass when the shear velocity was 7 × 10 −3 m s −1 .…”
Section: Introductionmentioning
confidence: 99%